PENGARUH LIVE STREAMING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE SHOPEE - Puspita, Dila (UM. Bengkulu, 2025)
In today's evolving era, many changes occur with various products emerging to meet market demands, leadi ng many women to enhance their beauty by caring for their skin and face. One common way women take care of their skin and face is by using skincare and body care products. The use of these products can boost women's self-confidence, as they help maintain healthy and well-cared- for skin and facesThis study aims to examine the influence of celebrity testimonials in live streaming and brand image on purchase decisions on Shopee E-commerce, with a case study on Scarlett Whitening products in Cempaka Permai Village, Gading Cempaka District, Bengkulu City This research is a quantitative descriptive study, with the population consisting of Scarlett Whitening product users in the area. The sampling method used was proportional sampling, with a total of 110 respondents. Data collection was carried out using questionnaires Data analysis techniques included multiple linear regression analysis, the coefficient of determination, and hypothesis testing. Based on the processed data, the regression equation obtained using SPSS 25 is: Y2389 0.216 X1 +0.770 X2 ei, with an R Square (R³) value of 0.878. This value indicates that the independent variables contribute 87 8% to influencing the dependent variable. The hypothesis test results show that live streaming and brand image together have a positive and significant effect on purchase decisions for Scarlett Whitening users in Cempaka Permai Village, Gading Cempaka District, Bengkulu City. Keywords: Live Streaming, Brand Image, and Purchase Decision.